كفاءة معلمي اللغة العربية في مواجهة تحديات العولمة - Rizki Abdurahman; Uus Ruswandi; Muhamad Erihadiana (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2024)
This study aims to describe the competence of Arabic language educators in facing the challenges of globalization, both standard competence and complementary competence. This is considered important because all educators are faced with the era of globalization which is increasingly growing rapidly. This study used a qualitative descriptive approach. The data collection technique used is documentation. Data analysis techniques are carried out by descriptive analysis. The results of this study explain that in facing the era of globalization, Arabic language educators must have self-awareness about their roles, functions, duties, responsibilities, and obligations as educators. He must have standard competencies that have been formulated in the Law including paedagogic competence, personality competence, social competence, and professional competence. Complementary competencies that must be possessed in facing the challenges of globalization are the ability to adapt to the development of science and technology, information media, multiculturalism, and have a positive character.